2010
DOI: 10.1111/j.1365-313x.2010.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry screening reveals widespread diversity in trichome specialized metabolites of tomato chromosomal substitution lines

Abstract: Glandular secreting trichomes of cultivated tomato (Solanum lycopersicum) and close relatives produce a variety of structurally diverse volatile and non-volatile specialized (‘secondary’) metabolites, including terpenes, flavonoids and acyl sugars. A genetic screen is described here to profile leaf trichome and surface metabolite extracts of nearly isogenic chromosomal substitution lines covering the tomato genome. These lines contain specific regions of the Solanum pennellii LA0716 genome in an otherwise ‘wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
219
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(234 citation statements)
references
References 59 publications
12
219
1
1
Order By: Relevance
“…Terpenes are stored in glandular trichomes of Solanum lycopersicum leaves and are released even in physiological conditions at a level of 0.5 nmol m -2 s -1 which is in accordance with data obtained by Schimiller et al [32,33]. The emissions consisted of α-pinene, camphene, 2-carene, α-phellandrene, limonene, β-phellandrene, (E)-β-ocimene and terpinolene as have been previously reported by Jensen et al [21] and Copolovici et al [16].…”
Section: The Influence Of Soil Salinity On Volatile Organic Compoundssupporting
confidence: 91%
“…Terpenes are stored in glandular trichomes of Solanum lycopersicum leaves and are released even in physiological conditions at a level of 0.5 nmol m -2 s -1 which is in accordance with data obtained by Schimiller et al [32,33]. The emissions consisted of α-pinene, camphene, 2-carene, α-phellandrene, limonene, β-phellandrene, (E)-β-ocimene and terpinolene as have been previously reported by Jensen et al [21] and Copolovici et al [16].…”
Section: The Influence Of Soil Salinity On Volatile Organic Compoundssupporting
confidence: 91%
“…Published studies revealed major differences in trichome metabolite accumulation (15,25,26,29) in several introgression lines (ILs), which have regions of the S. pennellii LA0716 genome substituted in place of the S. lycopersicum M82 genome (31). Rescreening the ILs by liquid chromatography-time of flight mass spectrometry (LC-ToF MS) identified a more subtle phenotype: accumulation of two lowabundance species in IL4-1 not seen in the M82 parent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, acylsugars are a group of structurally related specialized metabolites produced in plants of the nightshade family-the Solanaceae (9,10). Characterized examples in the tomato group of Solanum consist of either a glucose or a sucrose backbone with three to four aliphatic acyl groups of varying carbon numbers ranging from 2 to 12 esterified to the sugar hydroxyl groups (11)(12)(13)(14)(15). Nicotiana attenuata acylsucroses are at the center of a multitrophic defense interaction where they are metabolized to volatile fatty acids by Manduca sexta larvae, and these airborne products attract predatory ants (6).…”
mentioning
confidence: 99%
“…Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013). Metabolic diversity between different tissues might arise from differences in spatial-temporal expression of genes (Kim et al, 2012;Thatcher et al, 2014) and in some cases by duplicate genes that display spatially or temporally distinct expression patterns (Toubiana et al, 2012;Matsuba et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the enormous diversity of specialized metabolites in plants comes from modifications or decorations of core structures by different tailing reactions such as acylation (Bontpart et al, 2015), glycosylation (Bowles et al, 2005), methylation (Lam et al, 2007), and so on (Schwab, 2003). In addition, many studies have revealed that plant specialized metabolites accumulate with tissue specificity (Schilmiller et al, 2010;McDowell et al, 2011;Kim et al, 2012;Toubiana et al, 2012;Watanabe et al, 2013;Dong et al, 2015;Wen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%